Genomic exploration of Sesuvium sesuvioides: comparative study and phylogenetic analysis within the order Caryophyllales from Cholistan desert, Pakistan - Nida Javaid; Musarrat Ramzan; Shagufta Jabeen; Muhammad Nadeem Shah; Subhan Danish; Abdurahman Hajinur Hirad (BMC Plant Biology, 2023)
Abstract Background The Aizoaceae family’s Sesuvium sesuvioides (Fenzl) Verdc is a medicinal species of the Cholistan desert, Pakistan. The purpose of this study was to determine the genomic features and phylogenetic position of the Sesuvium genus in the Aizoaceae family. We used the Illumina HiSeq2500 and paired-end sequencing to publish the complete chloroplast sequence of S. sesuvioides. Results The 155,849 bp length cp genome sequence of S. sesuvioides has a 36.8% GC content. The Leucine codon has the greatest codon use (10.6%), 81 simple sequence repetitions of 19 kinds, and 79 oligonucleotide repeats. We investigated the phylogeny of the order Caryophyllales’ 27 species from 23 families and 25 distinct genera. The maximum likelihood tree indicated Sesuvium as a monophyletic genus, and sister to Tetragonia. A comparison of S. sesuvioides, with Sesuvium portulacastrum, Mesembryanthemum crystallinum, Mesembryanthemum cordifolium, and Tetragonia tetragonoides was performed using the NCBI platform. In the comparative investigation of genomes, all five genera revealed comparable cp genome structure, gene number and composition. All five species lacked the rps15 gene and the rpl2 intron. In most comparisons with S. sesuvioides, transition substitutions (Ts) were more frequent than transversion substitutions (Tv), producing Ts/Tv ratios larger than one, and the Ka/Ks ratio was lower than one. We determined ten highly polymorphic regions, comprising rpl22, rpl32-trnL-UAG, trnD-GUC-trnY-GUA, trnE-UUC-trnT-GGU, trnK-UUU-rps16, trnM-CAU-atpE, trnH-GUG-psbA, psaJ-rpl33, rps4-trnT-UGU, and trnF-GAA-ndhJ. Conclusion The whole S. sesuvioides chloroplast will be examined as a resource for in-depth taxonomic research of the genus when more Sesuvium and Aizoaceae species are sequenced in the future. The chloroplast genomes of the Aizoaceae family are well preserved, with little alterations, indicating the family’s monophyletic origin. This study’s highly polymorphic regions could be utilized to build realistic and low-cost molecular markers for resolving taxonomic discrepancies, new species identification, and finding evolutionary links among Aizoaceae species. To properly comprehend the evolution of the Aizoaceae family, further species need to be sequenced.